Estudo comparativo da densidade radiográfica de diferentes cimentos odontológicos restauradores à base de ionômero de vidro. - MELO, áureo Honorato e (2007)
Glass ionomer cements are generally represented by a combination of a powder, which main components are alumina (Al2O3 ), silica (Si2O3 ) and calcium fluoride (CaF2 ), and a liquid, which is an aqueous solution basically compound of polyacrilic acid and tartaric acid. Its excellent features have been described since the 1960 s, and some of these are the radiopacity and fluoride release. The aim of this work is to study the radiopacity measured by radiographic exposures of the following restorative glass ionomers: Vidrion R (SS White Manufacturing Ltd, Gloucester, England); Chemfil (DENTSPLY DeTrey, Konstanz, Germany); Vitro Molar (DFL); Maxxion R (FGM Dental products Ltd); Riva self cure powder and liquid and Riva self cure in capsules (Riva SC, SDI Ltd, Bayswater, Australia) and to make comparisons among them. Then, different radiographic densities from an aluminum scale were attained and they could be compared and used in the clinical work. The specimens were made using standard glass plates (25,4 x 76,2 x 1,0 mm) manufactured by Global Trade Technology and they were perforated by a 5mm bur (number 5, Black & Decker, Brazil) especially used for glass. For the radiopacity evaluation, the samples were radiographed using three different types of films, which are the following: Kodak Dental Intraoral ESpeed Film (EASTMAN KODAK Co., Rochester, N.Y.); Contrast DFL DV-58 (DFL Ltd); and Agfa Dentus M2 Confort (Heraeus Kulzer Inc.). A 99,5% pure aluminum step wedge and a Gnatus XR 6010 X-ray equipment were utilized in this work. The data were collected by 5 examiners, who were properly calibrated, and analyzed by Friedman and Kolmogorov-Smirnov tests. The results showed no statistical differences among the averages of each examiner comparing the cements and the films. And the results also showed that all the cements present radiographic density average values below 1.